“Prevalence and Clinical Profile of Chicken pox among student nurses among Tertiary Care Hospital, Western Maharashtra” - Arati, Kirole; Gholap, Manisha; Shinde, Mahadeo; Katti, Anagha (International Journal of Psychosocial Rehabilitation, 2020)
Background: Varicella (chickenpox) is a highly contagious disease that is caused by the varicella-zoster virus (VZV), a ubiquitous human α herpesvirus. Chickenpox can cause serious complications and even death in persons without any risk factors. Outbreaks of chickenpox are collected from 50 student nurses’ medical record files for the study from the hospital during this experience. Objectives: 1. To assess the clinical profile of student nurses affected with chickenpox at Tertiary Care Hospital, Western Maharashtra. 2. To determine the prevalence of chickenpox pox among student nurses at Tertiary Care Hospital, Western Maharashtra. 3. To find the association between selected clinical profiles and selected socio-demographic variables of student nurses tertiary care hospital in Western Maharashtra. Materials and Methods: The present study was a retrospective record-based study where 50 student nurses suffering from chickenpox were observed with special reference to unusual complications and outcomes. Results: Among 50 subjects were between age group 18 years 29 ( 58%) , while 50 (100%) were females whereas residential area Kerala 48 (96%) and maximum subjects in Christian religion 48 (96%) and in academic year 1st year students suffering 30 (60%)and unmarried 50 (100%). In the summer season, 34 (68 %) students had chickenpox, and 13 (26%) cases were found in the monsoon season. A maximum of 49 (98%) students are having 8-10 days of illness, and no specific investigation done. All 50 students were given the first line of treatment. Conclusions: In present study we concludes that majority of the Kerala students suffer from chickenpox when they are exposed to environment of Western Maharashtra So compulsory childhood varicella vaccination, including vaccination of risk groups and susceptible individuals, is essential to reduce the incidence of chickenpox, associated complications, and subsequent death.